2017
DOI: 10.1002/advs.201700089
|View full text |Cite
|
Sign up to set email alerts
|

An Important Function of Petrosiol E in Inducing the Differentiation of Neuronal Progenitors and in Protecting Them against Oxidative Stress

Abstract: Insufficient endogenous neurotrophin supply contributes to neurodegeneration. Meanwhile, neuronal injuries are also attributed to oxidative stress upon toxin exposure. Thus, reconstruction neurite extension and antioxidative stress are the potential strategies for ameliorating neuronal injuries. However, there is no well‐defined therapeutic developed in this regard. In search of such therapeutics, Petrosiol E is identified here as a potent inducer to guide the differentiation of neuronal progenitor cells. Petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…24 Finally, one-pot global deprotection of 17a,b were achieved with 3 N HCl in reuxing ethanol, delivering petrosiol B (2) in 97% yield and petrosiol D (4) in 98% yield, respectively. The spectroscopic data ( 1 H, 13 C NMR, and HRMS) and specic rotation data of both synthetic petrosiol B and petrosiol D were in good agreement with those of the natural products (see the ESI †).…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…24 Finally, one-pot global deprotection of 17a,b were achieved with 3 N HCl in reuxing ethanol, delivering petrosiol B (2) in 97% yield and petrosiol D (4) in 98% yield, respectively. The spectroscopic data ( 1 H, 13 C NMR, and HRMS) and specic rotation data of both synthetic petrosiol B and petrosiol D were in good agreement with those of the natural products (see the ESI †).…”
Section: Resultssupporting
confidence: 68%
“…With the synthetic petrosiol E in hand, we studied its molecular mechanism in stimulating neuronal differentiation and antioxidative stress in PC12 neuronal progenitor cells. 13 We found that petrosiol E could stimulate the mitogen-activated protein kinase and serine/tyrosine kinase signaling to enhance the activity of Nrf2. We also identied a dual role of petrosiol E in potentiating the differentiation of neuronal progenitors and in protecting them against arsenic-induced oxidative stress in PC12 cells.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations